Constitutional rights and obligations of citizens towards the environment under sustainable development conditions (Ius Novum, 2024)
The aim of this article is to determine the status of citizens’ rights to a “clean environment” and their obligations towards the environment in the conditions of sustainable development in the light of international and national regulations. Therefore, the article analyzes three related aspects, i.e. human rights to a “clean environment”, obligations of citizens and public authorities towards the environment, and environmental protection in accordance with the principle of sustainable development. Human rights to a “clean environment” are constitutionally guaranteed and are derived from the Universal Declaration of Human Rights and the Rio de Janeiro Declaration “Environment and Development”. These rights are implemented by public authorities by ensuring ecological safety, use and protection of environmental resources in accordance with the principle of sustainable development. In addition, every citizen has obligations towards the environment, because he should take care of environmental resources and use them in accordance with the principles of environmental protection law. Based on the analysis of the doctrine and legal regulations in this area, a clear relationship was observed between the need to guarantee basic constitutional human rights to a “clean environment” by public authorities and the obligation of these entities towards the environment by protecting environmental resources in accordance with the principle of sustainable development. This should be done in such a way as to balance human rights to a “clean environment” with environmental rights to the continuity and sustainability of resources (natural balance) while guaranteeing economic development. An example of the implementation of these assumptions is the 2030 Agenda currently implemented in Poland and other EU countries.
Keywords: human rights, environmental protection law, constitutional obligations of public authorities, the principle of sustainable development, Agenda 2030 program